2020
DOI: 10.3390/ijms21134692
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Polypeptide in the Carotid Body—A History of Forty Years of Research. A Mini Review

Abstract: Vasoactive intestinal polypeptide (VIP) consists of 28 amino acid residues and is widespreadin many internal organs and systems. Its presence has also been found in the nervous structuressupplying the carotid body not only in mammals but also in birds and amphibians. The numberand distribution of VIP in the carotid body clearly depends on the animal species studied;however, among all the species, this neuropeptide is present in nerve fibers around blood vesselsand between glomus cell clusters. It is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…It is also known that VIP may be involved in the regulation of the secretory activity in the digestive tract and processes connected with immunological and/or inflammatory reactions [ 9 ]. Moreover, previous studies have reported that VIP participates in protective and adaptive processes leading to the maintenance of homeostasis during various pathological processes and ensuring the functions of the ENS in conditions changed by the disease process [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that VIP may be involved in the regulation of the secretory activity in the digestive tract and processes connected with immunological and/or inflammatory reactions [ 9 ]. Moreover, previous studies have reported that VIP participates in protective and adaptive processes leading to the maintenance of homeostasis during various pathological processes and ensuring the functions of the ENS in conditions changed by the disease process [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the neuronal substances that are widely distributed in the intestinal innervations, and which may be involved in mechanisms connected with enteropathies, is vasoactive intestinal polypeptide (VIP) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota produces various neuromodulators [•43, 57 ]. Among the neuronal compounds detected in the rat glomus cells are NO, enkephalins, neurotensins, neuropeptide Y, substance P, dopamine, GABA, vasoactive intestinal peptide and tyrosine hydroxylase [ 58 ]. The major catecholamine functional in the CB is dopamine which exerts inhibitory signals to both hypoxia-sensing and ventilatory efforts [ 9 ].…”
Section: Gut Microbiota-derived Circulating Metabolites Blunt Hypoxia-sensing In Covid-19mentioning
confidence: 99%
“…This has led to the concept of “neurovascular unit (NVU)” (reviewed in Iadecola, 2017). The SCN produces neuropeptides known to regulate vascular activities including vasopressin (AVP), vasoactive intestinal polypeptide, gastrin-releasing peptide, and angiotensin II (Ang II), among others (Abrahamson and Moore, 2001; Azushima et al, 2020; Gonkowski, 2020; Japundžić-Žigon et al, 2020; Qu et al, 2018). However, how these vasoactive peptides participate in the neurovascular coupling within the SCN is barely understood, partly due to a limited understanding of the SCN vasculature in relation to its peptidergic phenotypes.…”
mentioning
confidence: 99%